2012
DOI: 10.1134/s1064229312020044
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure of microbial community in soils with different degrees of salinization using T-RFLP and real-time PCR techniques

Abstract: Molecular methods were used to study variation in the taxonomic structure of bacterial, archaeal, and fungal communities in soil samples taken along a salinity gradient from a solonchak in the vicinity of Lake Akkol' (Shingirlau, Kazakhstan). Soils from arable fields located 195 km from the solonchak served as the control. Total DNA was isolated from every sample and analyzed by T RFLP and real time PCR. Saliniza tion was found to be the main ecological factor determining the structure of soil microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 26 publications
2
19
0
1
Order By: Relevance
“…This was an indication of increased osmotic pressure (salt stress), that would possibly make the substrate draw water out of the cells of microorganism, hence death in the media or reduced chance of survival. This observation is in agreement with Andronov et al (2012), that salt stress can reduce microbial activities, biomass and community structures in soil or substrate as in this case. Results are also in agreement with the observation of Yan et al (2015) on the reduction of soil microbes with the influence of soluble salts in the substrate.…”
Section: Discussionsupporting
confidence: 93%
“…This was an indication of increased osmotic pressure (salt stress), that would possibly make the substrate draw water out of the cells of microorganism, hence death in the media or reduced chance of survival. This observation is in agreement with Andronov et al (2012), that salt stress can reduce microbial activities, biomass and community structures in soil or substrate as in this case. Results are also in agreement with the observation of Yan et al (2015) on the reduction of soil microbes with the influence of soluble salts in the substrate.…”
Section: Discussionsupporting
confidence: 93%
“…It is agreed in the literature that the driving factors for the evolution of a microbial community structure largely depend on the environmental gradient to which the communities are subjected or imposed under experimentally 62 . Organic C 63 , N availability 64 , pH 65 , salinity 66 67 , moisture 68 and many other abiotic factors influence the microbial community structure in soil. Despite this, the edaphic gradients were not found to equally impact the community structure in the tailings of this study, with soluble N and water content being the best controllers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies ( 2 , 3 , 7 , 17 , 22 ) demonstrated that high salinity reduces microbial activity and changes the microbial community structure. Kartal et al ( 9 ) reported two possible outcomes of the adaptation of a biomass to salinity: (i) the acclimation of the existing population or (ii) a population shift.…”
mentioning
confidence: 93%